Reichsparteitag-Nürnberg Ansichtskarte Postkarte Nürnberger Burg... - Auteur inconnu (Wikimedia Commons, 1936)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag-Nürnberg Ansichtskarte Postkarte Nürnberger Burg SA-Mann Hakenkreuz Fahne Wappen NSDAP Propaganda Nazi Party Nuremberg Rally 1936 Postcard Photo-Hoffmann Munich no. 36-9 Uncredited artist No known copyright 675498-00. " Nuremberg Rally " (Reichsparteitag-Nürnberg). Postcard showing a painting of a uniformed standard bearer of the Sturmabteilung (SA) with a Swastika flag, coat of arms of Nuremberg, Nuremberg Castle, etc. | No signature (uncredited artist) | published by Verlag Photo-Hoffmann, Munich, Nazi Germany, card no. 36/9 | Nazi Party (NSDAP) propaganda
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale